Survey of perceptions and practices among Canadian gastroenterologists regarding the prevention of venous thromboembolism for hospitalized inflammatory bowel disease patients - Razik, Roshan (Pulsus Group Inc, 2012)
BACKGROUND: Patients with inflammatory bowel disease (IBD) who are hospitalized with disease flares are known to be at an increased risk of venous thromboembolism (VTE). This is a preventable complication; however, there is currently no standardized approach to the prevention and management of VTE. OBJECTIVES: To characterize the opinions and general prophylaxis patterns of Canadian gastroenterologists and IBD experts. METHODS: A survey questionnaire was sent to Canadian gastroenterologists affiliated with a medical school or IBD referral centre. Participants were required to be practicing physicians who had completed all of their training and had been involved in the care of IBD patients within the previous 12 months. Various clinical scenarios were presented and demographic data were solicited. RESULTS: The majority of respondents were practicing in an academic setting (95%) and considered themselves to be IBD experts or subspecialists (71%). Eighty-three per cent reported providing VTE prophylaxis most, if not all of the time, and most (96%) used pharmacological prophylaxis alone, usually heparin or one of its analogues. There was less consistency among respondents with respect to whether IBD patients in remission, but admitted for another condition, should be given prophylaxis. There was also less agreement regarding the duration of anticoagulation in patients with confirmed VTE. CONCLUSION: There was a general consensus among academic gastroenterologists that IBD inpatients are at an increased risk for VTE and would benefit from VTE prophylaxis. However, areas of uncertainty still exist and the IBD community would benefit from evidence-based clinical practice guidelines to standardize the management of this important problem.